Ground-Independent UAV Quantitative Mapping and In Situ Experimental Validation for Coral Reef Habitats - Enze Wang; Huaguo Zhang; Yunhan Ma; Han Tong; Juan Wang; Wenting Cao; Dongling Li (IEEE Journal of Selected Topics in Applied Earth Observations and Remote Sensing)
Optically shallow waters, which host ecosystems like coral reefs, are characterized by complex radiative transfer pathways. Surface reflectance derived from remote sensing in optically shallow waters is influenced by water depth, water quality, and bottom reflectance. Consequently, in situ measurements of these parameters are often challenging to match directly with remote sensing-derived reflectance. However, this also highlights the potential for estimating these environmental parameters from reflectance data. This study proposes a unmanned aerial vehicle (UAV) quantitative mapping approach for coral reef habitats using a drone and a multispectral camera, independent of ground-based in-situ measurements. It also proposes an in-situ experimental design and instrumentation for validating optical parameters. In the study area, water depths between 0 and 6 m were well detected. UAV-derived depths achieved a coefficient of determination (R2) of 0.910 and an overall RMSE of 0.410 m compared to echo-sounding results. The estimated optical attenuation coefficients for the BGR channels at representative depths were 0.424, 0.32, and 0.647 m-1, respectively, corresponding to various natural waters with chlorophyll concentrations of approximately 0.2–0.5 mg/m3. This aligns well with the in situ chlorophyll measurements, which had an average value of 0.38 mg/m3. Remote sensing-derived bottom reflectance aligns with in situ measurements in both magnitude and spectral shape. Overall, the proposed UAV quantitative mapping method enhances the efficiency and diversity of coral reef monitoring, while the in situ survey approach ensures accuracy. Both aerial and in-situ methods hold promise for routine coral reef research and conservation efforts.